New modes of managing grand challenges: Cross-sector collaboration and the refugee crisis of the Asia Pacific. Issue 4 (November 2019) - Quayle, Annette; Grosvold, Johanne; Chapple, Larelle
Grand challenges are complex, large-scale problems requiring collaborative, multidisciplinary attention. Cross-sector collaboration can potentially play a significant role in addressing these challenges by capturing the diverse vision, experience, knowledge and resources of different sectors. Yet we still know little of the inter-organisational dynamics of how sectors work together to address grand challenges and the consequences of doing so. Our article contributes to the literature at the intersection of management and grand challenges by identifying how cross-sector collaborations can be used more effectively to address grand challenges. Drawing on a study of Australia's offshore processing of refugees, we highlight the inter-organisational issues that emerge and develop a collaborative governance framework to overcome these problems and guide future cross-sector collaborations directed at grand challenges. JEL Classification:M5, H11